Handbook of Computational Economics volumen 3 - Schmedders, Karl; Judd, Kenneth L. (Amsterdam [etc.] North-Holland, 2014)
With computational power increasing in hardware and algorithms, many economists are closing the gap between economic practice and the frontiers of computational mathematics.
Keywords: Economía matemática; Algoritmos; Simulación (Informática)